PEMILIHAN PROFESI AKUNTAN PUBLIK DENGAN NILAI-NILAI SOSIAL SEBAGAI PEMODERASI PADA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS SAMUDRA - Al Miftahul Husna; Afrah Junita; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to determine the effect of financial rewards, professional recognition and labor market considerations on the interest in choosing the public accountant profession with social values as a moderating variable for students of the Accounting study program at the Faculty of Economics, Universitas Samudra. This research data is primary data using a questionnaire as a tool to collect data. The population in this study were students of the accounting study program at the Faculty of Economics, Universitas Samudra who had reached semester 7 (seven) at the time this research was conducted. The statistical analysis used in this research is multiple linear regression analysis using SPSS. The research method used is quantitative research and analyzed using Moderated Regression Analysis (MRA). The results of this study indicate that Financial Awards, professional recognition, labor market considerations have a positive and significant effect on the interest in choosing the public accounting profession partially, while social values have no effect on the interest in choosing the public accounting profession. Furthermore, social values can moderate the effect of financial rewards on the interest in choosing the public accounting profession, social values can moderate the effect of professional recognition on the interest in choosing the public accounting profession, social values cannot moderate the effect of labor market considerations on the interest in choosing the public accounting profession and social values can moderate the effect of financial rewards, professional recognition and labor market considerations together on the interest in choosing the public accounting profession.